Not the witch you wed eaudiobook - Asher, April (Supernatural Singles, 2022)
Magic-less witch Violet Maxwell wants nothing to do with alpha wolf shifter Lincoln Thorne—the man who broke her fragile teenage heart. But when the two of them are forced by arcane Supernatural Laws to find mates, Violet and Lincoln agree to fake-date their way to a fake-mating in order to conjure themselves some time. The joke's on them. When old feelings make a reappearance—along with Violet's magic—they both realize there's nothing fake about their feelings. But there are old secrets and looming threats that could snatch away their happily ever after, again. One thing's for sure: magic doesn't make dating and love any easier. In this start to a bewitching new paranormal series about being sexy, single, and supernatural in New York City, April Asher brings all the hilarity and sweet, sexy moments you love in a romantic comedy—plus a fun dose of magic.